Ab interno gel implant in patients with primary open angle glaucoma and pseudoexfoliation glaucoma - Fritz H. Hengerer; Gerd U. Auffarth; Timur M. Yildirim; Ina Conrad-Hengerer (BMC Ophthalmology, 2018)
Abstract Purpose To compare efficacy and safety results of an ab interno gel implant in patients with pseudoexfoliation glaucoma (PXG) and primary open angle glaucoma (POAG). Methods Retrospective analysis of the medical records of 110 consecutive eyes with open angle glaucoma who had received a XEN45 gel implant between March 2014 and June 2015. Intraocular pressure course, number of glaucoma medications, the need for additional intervention (including needling) and complications were evaluated until 12 months postoperatively. Results Data of 67 eyes with POAG and 43 eyes with PXG were analyzed. At 12 months postoperatively, the mean IOP had significantly decreased by 54.0% from preoperatively 31.85 ± 8.5 mmHg to 13.99 ± 2.6 mmHg in the POAG group, (p = 0.000; Wilcoxon test), and by 55.2% from 31.63 ± 9.0 mmHg to 13.28 ± 3.1 mmHg in the PXG group (p = 0.000; Wilcoxon test). The mean number of anti-glaucoma medications had significantly decreased from 3.25 ± 0.8 at baseline to 0.3 ± 0.7 medications at 12 months postoperatively in POAG eyes (p = 0.000; Wilcoxon test), and from 3.05 ± 1.0 to 0.3 ± 0.6 medications in PXG eyes (p = 0.000; Wilcoxon test). Hypotony (IOP ≤ 6 mmHg) was observed in 2 POAG eyes (3.0%) and in 5 PXG eyes (11.7%) at 1 month but normalized in all eyes at 12 months postoperatively. Severe complications were not observed. No statistically significant differences were found between PXG eyes and POAG eyes. Conclusion Our data indicate that the XEN45 gel implant provides significant and comparable reduction in IOP and anti-glaucoma medication during the one-year follow-up period in POAG as well as PXG eyes. This suggests that it may be a noteworthy alternative to traditional filtering procedures in patients with POAG and PXG respectively.